2019
DOI: 10.36927/2079-0325-v27-is4-2019-11
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Quality of Life Indices in Case of Metabolic Syndrome in Patients with Paranoid Schizophrenia on the Background of Atypical Neuroleptic Agents Application and Improvement of Comorbidity

Abstract: The objective of the research was to study the features of quality of life dynamics depending on clinical and psychopathological symptoms in patients with paranoid schizophrenia asso ciated with metabolic syndrome on the background of long-term neuroleptic therapy and to study the eff ectiveness of concomitant corrective therapy. 140 patients with paranoid schizophrenia (F20.0) were examined and divided into three groups. Group I included 40 patients who received haloperidol at an ave rage daily dose of 4.6 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…As a result, this leads to negative consequences in their physical and psychological state such as deterioration in health, well-being, mood, and performance; and weakening of cognitive functions. The signs of psycho-physiological and psycho-emotional disorders such as chronic stress, anxiety, grumpiness, depression, fatigue, low activity, reduced performance, and violations in the social sphere appear (Romash, 2019;2020). These disorders are called "winter-over syndrome".…”
Section: Introductionmentioning
confidence: 99%
“…As a result, this leads to negative consequences in their physical and psychological state such as deterioration in health, well-being, mood, and performance; and weakening of cognitive functions. The signs of psycho-physiological and psycho-emotional disorders such as chronic stress, anxiety, grumpiness, depression, fatigue, low activity, reduced performance, and violations in the social sphere appear (Romash, 2019;2020). These disorders are called "winter-over syndrome".…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the life expectancy, it is, on average, 10 years shorter (by 30% according to other estimates) in patients with schizophrenia. After conducting a comprehensive analysis of scientific researches, scientists have concluded that patients with schizophrenia have a higher prevalence of cardiovascular disease, obesity, diabetes, osteoporosis in comparison with the general population [11]. Such comorbid somatic diseases in case of schizophrenia have a more acute course, a significant impact on the course of the underlying disease, the development of complications.…”
mentioning
confidence: 99%